WINGS OF WORDS: A STRUCTURED USR INTERVENTION FOR GAME-BASED ENGLISH LANGUAGE LEARNING - Jahaya, Nadira M.; Ibrahim, Syazliyati; Shafiai, Noor ‘Izzati Ahmad; Syed Shaharudin, Sharifah Syakila; Nordin, Razanawati (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This paper is a study on Wings of Words, a half-day University Social Responsibility (USR) initiative organised to support English language enhancement among underprivileged students using game-based pedagogy. The project was designed to improve English language among children from underserved communities, to promote foundational English language skills in an appealing, inclusive, and interactive manner. Organised by university faculty and student volunteers, the programme implemented three structured activity stations that are Giant Block, Word Treasure, and Blockbuster aimed at enhancing the students’ vocabulary acquisition, listening comprehension, and verbal communication. The games were carefully planned to align with language learning objectives while encouraging active participation, teamwork and learner autonomy. Data was collected through a questionnaire to assess engagement levels and expected learning outcomes. Findings imply that the integration of play-based methods not only amplified student motivation and participation but also enabled meaningful language use in context. Additionally, the project offered university students essential experiential learning opportunities in community service. The Wings of Words project underscores the potential of short-term, university-led interventions to create a measurable impact on language learning in marginalised communities. It also highlights the shared benefits of USR activities for both learners and facilitators. The paper concludes by discussing pedagogical implications and recommendations for planning such initiatives in wider educational contexts.